2022
DOI: 10.1002/dev.22359
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxytocin on parenting behaviors and parent–child bonding: A systematic review

Abstract: Oxytocin (OT) plays a pivotal role in early parent-child relationship formation and bonding that is critical for the social, cognitive, and emotional development of the child.Therefore, this systematic review aims to consolidate all available evidence regarding the associations of parental OT concentration levels with parenting behavior and bonding within the past 20 years. A systematic search was conducted in five databases from 2002 to May 2022, and 33 studies were finalized and included. Due to the heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Findings indicate that higher levels of oxytocin are associated with the early stages of a romantic relationship ( Schneiderman et al, 2012 , 2014 ; Ulmer-Yaniv et al, 2016 ) and during maternal love, such as following mother–child contact ( Scatliffe et al, 2019 ) and during pregnancy ( Levine et al, 2007 ). A recent systematic review found substantial evidence for oxytocin’s role in human parenting behaviors and parent–child bonding ( Shorey et al, 2023 ).…”
Section: A Theory Of Co-opting Mother-infant Bondingmentioning
confidence: 99%
“…Findings indicate that higher levels of oxytocin are associated with the early stages of a romantic relationship ( Schneiderman et al, 2012 , 2014 ; Ulmer-Yaniv et al, 2016 ) and during maternal love, such as following mother–child contact ( Scatliffe et al, 2019 ) and during pregnancy ( Levine et al, 2007 ). A recent systematic review found substantial evidence for oxytocin’s role in human parenting behaviors and parent–child bonding ( Shorey et al, 2023 ).…”
Section: A Theory Of Co-opting Mother-infant Bondingmentioning
confidence: 99%
“…Interestingly, no associations were found between OT in maternal breast milk and infant saliva. Some studies identified links between mothers' and infants' OT levels or fathers' and infants' OT levels [ 23 , 38 , 67 ]. One possibility is that breastfeeding and sensitive, non-anxious maternal caregiving evoke OT secretion through the oral suckling stimulus, skin-to-skin touch, and a close affiliative relationship [ 68 ], but much further research is needed to examine the transfer of OT from mother to child through non-identical fractions, such as breast milk to saliva.…”
Section: Discussionmentioning
confidence: 99%